Punitiveness in Australia: electronic monitoring vs the prison - Kornhauser, Ryan (Crime, law and social change, 2014)
Internationally, the 200 year honeymoon with the prison may be ending. Research showing that imprisonment is ineffective in reducing crime is finally being heeded by some conservative governments committed to cost cutting. But, as this case-study of Victoria, Australia, again highlights, punishment regimes are neither universal nor rational. Bucking the trend, prison numbers in Victoria have increased dramatically over the last decade and are set to rise higher. The lingering lure of the prison here, we argue, is a manifestation of Australia’s colonial history in which punitiveness has always competed with pragmatic innovation. Although the research findings are inconclusive, we contend that Electronic Monitoring (EM), while differently fraught, better meets the key objectives of sentencing. Using a counterfactual social science thought experiment in the form of an imagined Cabinet submission, we show how political decision makers might be persuaded to effect a shift from prison to EM if it is framed within the competing visions of Australian national identity. We argue that understanding how social policy decisions are made sharpens the scholarly research agenda and also highlights how the convergence of a unique set of non-rational cultural assumptions can shape major shifts (or near misses) in the history of punishment in a particular society.